Ranking of Universities in the United Arab Emirates: Exploring a web-based technique - Govender, K. K.; Nel, E. (South African Journal of Higher Education, 2021)
This study investigated university rankings in the UAE within the context of the challenges facing higher education globally in the 21st century, by using the Webometric ranking methodology. Data was collected and analysed on the top 20 UAE universities. It was apparent that the UAE universities do not perform as well as expected in the Webometrics ranking, when compared with peer countries. The ratings are slightly below that which is expected, especially when one considers measures such as research publications. Strategies to improve performance using the Webometrics indicators could have a positive impact on the UAE universities. Improvements in communicating research and their web presence is likely to move the UAE universities up the Webometrics rankings, and their academic reputation in the country.